1992
DOI: 10.1524/ract.1992.5859.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of Radionuclide Diffusion in Site-Specific Sediment/Groundwater Systems

Abstract: Results gained by diffusion experiments in sediment/ groundwater systems from selected sites around the planned repositories for radioactive wastes in Germany and in mineral landfill liners are given. The tracer nuclides used were U-233, Ra-226, Pb-210, Ni-63 and Cd-109. It is shown that, among other parameters, diffusion coefficients and distribution coefficients could be derived from concentration-time curves. Moreover, experiments confirm that the diffusion behaviour of nuclides such as Pb and Ni can be enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…(15) the effect of humic colloids on the migration of radionuclides has been observed in dynamic laboratory experiments. Thus, it could be shown by Meier et al (1992) that the rate of diffusion of Pb 2+ through sandy sediments (Gohy 2220) increases significantly in the presence of Aldrich humic colloids. Additionally, column experiments with the water/sediment system Gohy 1012 rich in humic colloids (Kim, 1991) have demonstrated that mobilities of Th 4+ and Pb 2+ are greater than those anticipated in a two-phase system.…”
Section: Mobility Of Colloid-associated Radionuclidesmentioning
confidence: 99%
See 1 more Smart Citation
“…(15) the effect of humic colloids on the migration of radionuclides has been observed in dynamic laboratory experiments. Thus, it could be shown by Meier et al (1992) that the rate of diffusion of Pb 2+ through sandy sediments (Gohy 2220) increases significantly in the presence of Aldrich humic colloids. Additionally, column experiments with the water/sediment system Gohy 1012 rich in humic colloids (Kim, 1991) have demonstrated that mobilities of Th 4+ and Pb 2+ are greater than those anticipated in a two-phase system.…”
Section: Mobility Of Colloid-associated Radionuclidesmentioning
confidence: 99%
“…rock salt may reach waste packages so that nuclides might be released (Warnecke et al, 1984(Warnecke et al, , 1994. Therefore, for the performance of a longterm safety assessment the barrier function of the geological formations overlying the salt dome have been studied by batch, column and diffusion experiments (Lieser et al, 1990;Meier et al, 1992Meier et al, , 1993Meier et al, , 1994Meier et al, , 1995Hollmann and Tittel, 1993;Kim et al, 1994;Warnecke et al, 1994).…”
mentioning
confidence: 99%
“…it, = 1.01 · 10". Initial concentration range: 1.6 · ΙΟ" 10 sorption and desorption ratios decrease as nuclide concentration increases. In accordance with many adsorption studies [2,6,15,18] the Freundlich and Langmuir models were found to describe this effect.…”
Section: Influence Of Nuclide Concentrationmentioning
confidence: 99%
“…This effect is very important to contaminant migration because variation of nuclide species by organic complexants may significantly reduce the sorption behavior of certain radionuclides such as Co, Ni, Pb and actinides [10,12,23,[27][28][29][30][31].…”
Section: Influence Of Complex Forming Ligandsmentioning
confidence: 99%
See 1 more Smart Citation